All-offspring natal philopatry in a Neotropical bat - Chaverri Echandi, Gloriana (2011)
Natal dispersal is a strategy employed by individuals to avoid reproducing with close relatives. In most bats, incestuous matings are prevented by the departure of one sex; thus, all-offspring philopatry has rarely been recorded in these mammals. Here we present evidence of all-offspring philopatry to natal groups in a Neotropical insectivorous bat. Our results are derived from behavioural observations of a long-term, captureemarkerecapture study conducted on three populations of Spix’s disc-winged bat, Thyroptera tricolor. Results indicate that dispersal patterns of this species are characterized by low emigration rates (0.40e0.73 individuals per year), long residence times (492e1238 days) and high offspring retention of both sexes within natal groups. The retention of offspring resulted in groups being primarily composed of one or two matrilines. Our study is the first to demonstrate such high amounts of male and female natal philopatry coupled with limited spatial movements in bats. These dispersal patterns may be explained by morphological and ecological constraints associated with costly flight dynamics and significant variation in the distribution and quality of habitat, in addition to social benefits accrued by remaining affiliated with close kin.